Frog Foam Nest Protein Diversity and Synthesis. Issue 7 (27th July 2016) - Hissa, Denise Cavalcante; Bezerra, Walderly Melgaço; Freitas, Cléverson Diniz Teixeira De; Ramos, Márcio Viana; Lopes, José Luiz De Souza; Beltramini, Leila Maria; Roberto, Igor Joventino; Cascon, Paulo; Melo, Vânia Maria Maciel
ABSTRACT: Some amphibian species have developed a breeding strategy in which they deposit their eggs in stable foam nests to protect their eggs and larvae. The frog foam nests are rich in proteins (ranaspumin), especially surfactant proteins, involved in the production of the foam nest. Despite the ecological importance of the foam nests for evolution and species conservation, the biochemical composition, the long‐term stability and even the origin of the components are still not completely understood. Recently we showed that Lv‐RSN‐1, a 23.5‐kDa surfactant protein isolated from the nest of the frog Leptodacylus vastus, presents a structural conformation distinct from any protein structures yet reported. So, in the current study we aimed to reveal the protein composition of the foam nest of L. vastus and further characterize the Lv‐RSN‐1. Proteomic analysis showed the foam nest contains more than 100 of proteins, and that Lv‐RSN‐1 comprises 45% of the total proteins, suggesting a key role in the nest construction and stability. We demonstrated by Western blotting that Lv‐RSN‐1 is mainly produced only by the female in the pars convoluta dilata, which highlights the importance of the female preservation for conservation of species that depend on the production of foam nests in the early stages of development. Overall, our results showed the foam nest of L. vastus is composed of a great diversity of proteins and that besides Lv‐RSN‐1, the main protein in the foam, other proteins must have a coadjuvant role in building and stability of the nest.